2018
DOI: 10.1007/s40778-018-0110-3
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Roles of Connexin 43 in Stem Cell Niches

Abstract: Purpose of ReviewConsiderable progress has been made in the field of stem cell research; nonetheless, the use of stem cells for regenerative medicine therapies, for either endogenous tissue repair or cellular grafts post injury, remains a challenge. To better understand how to maintain stem cell potential in vivo and promote differentiation ex vivo, it is fundamentally important to elucidate the interactions between stem cells and their surrounding partners within their distinct niches.Recent FindingsAmong the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 151 publications
1
25
0
2
Order By: Relevance
“…Gap junctional communication is considered critical for the coordination of cellular functions within an epithelium. Studies have shown that Cx43 is implicated in various stem cell niches, or specialized microenvironments (Schofield, ; Genet et al ., ). Such microenvironments are essential for maintaining stem cells in a quiescent, self‐renewal, or activated state.…”
Section: Basal Cells As Potential Stem Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…Gap junctional communication is considered critical for the coordination of cellular functions within an epithelium. Studies have shown that Cx43 is implicated in various stem cell niches, or specialized microenvironments (Schofield, ; Genet et al ., ). Such microenvironments are essential for maintaining stem cells in a quiescent, self‐renewal, or activated state.…”
Section: Basal Cells As Potential Stem Cellsmentioning
confidence: 97%
“…Such microenvironments are essential for maintaining stem cells in a quiescent, self‐renewal, or activated state. Cx43 has been shown to regulate stem cell renewal in the brain, skin, bone marrow, mammary gland, and prostate (Genet et al ., ). While the role of Cx43 in maintaining basal cell renewal in the epididymis is unknown, it is nevertheless intriguing that in tissues where basal cells have been shown to act as stem cells, Cx43 plays a critical role in regulating stem cell renewal.…”
Section: Basal Cells As Potential Stem Cellsmentioning
confidence: 97%
“…Cx43, экспрессируемый БКЭ, участвует в создании специализированного микроокружения для различных типов стволовых клеток [18]. Было установлено, что Cx43 регулирует обновление стволовых клеток в головном мозге, коже, костном мозге, молочной железе и простате [18].…”
Section: бкэ как потенциальные взрослые стволовые клеткиunclassified
“…Cx43, экспрессируемый БКЭ, участвует в создании специализированного микроокружения для различных типов стволовых клеток [18]. Было установлено, что Cx43 регулирует обновление стволовых клеток в головном мозге, коже, костном мозге, молочной железе и простате [18]. Хотя роль Cx43 в обновлении БКЭ не установлена, известно, что в тканях, где базальные клетки действуют как стволовые клетки, Cx43 играет ключевую роль в регуляции обновления стволовых клеток.…”
Section: бкэ как потенциальные взрослые стволовые клеткиunclassified
“…In some tissues, such as the heart and uterus, these channels are of utmost importance for passing the electrical impulse from cell to cell, making these organs contract in a synchronized manner [30,31]. The channels are probably also involved in cellular homeostasis and growth control [32], possibly through interactions with numerous proteins involved in signaling and regulation [33][34][35]. Additionally, there are now strong indications that hemichannels are functional in their own right [36][37][38].…”
Section: Introductionmentioning
confidence: 99%